The hemodynamic effects of the LVAD outflow cannula location on the thrombi distribution in the aorta: A primary numerical study. Issue 133 (September 2016) - Zhang, Yage; Gao, Bin; Yu, Chang
Highlights: Although a growing number of patients undergo LVAD implantation for heart failure treatment, stroke, caused by the thrombus, is still the most devastating complication for patients who used LVAD. However, the hemodynamic effects of LVAD on the thrombosis distribution in the aorta are still unclear. This manuscript compared the differences of thrombus distribution in the aorta under two anastomotic position of LVAD outflow cannula in ascending aorta. The numerical study shows that the LVAD outflow cannular location could significantly change the hemodynamic states and the distribution of thrombus in the aorta. When the outflow cannula is anastomosed at the aortic anterior wall, the thrombus has a low probability to cause stroke compared with that anastomosed at the aortic anterior wall. The thrombus, coming from left ventricle, is easier to cause stroke than that is from LVAD. The difference in thrombus distribution may be caused by the hemodynamic difference under two configurations. Abstract: Although a growing number of patients undergo LVAD implantation for heart failure treatment, thrombi are still the devastating complication for patients who used LVAD. LVAD outflow cannula location and thrombi generation sources were hypothesized to affect the thrombi distribution in the aorta. To test this hypothesis, numerical studies were conducted by using computational fluid dynamic (CFD) theory. Two anastomotic configurations, in which the LVAD outflow cannula is anastomosed to the anterior and lateral ascending aortic wall (named as anterior configurations and lateral configurations, respectively), are designed. The particles, whose sized are same as those of thrombi, are released at the LVAD output cannula and the aortic valve (named as thrombiP and thrombiL, respectively) to calculate the distribution of thrombi. The simulation results demonstrate that the thrombi distribution in the aorta is significantly affected by the LVAD outflow cannula location. In anterior configuration, the thrombi probability of entering into the three branches is 23.60%, while that in lateral configuration is 36.68%. Similarly, in anterior configuration, the thrombi probabilities of entering into brachiocephalic artery, left common carotid artery and left subclavian artery, is 8.51%, 9.64%, 5.45%, respectively, while that in lateral configuration it is 11.39%, 3.09%, 22.20% respectively. Moreover, the origins of thrombi could affect their distributions in the aorta. In anterior configuration, the thrombiP has a lower probability to enter into the three branches than thrombiL (12% vs. 25%). In contrast, in lateral configuration, the thrombiP has a higher probability to enter into the three branches than thrombiL (47% vs. 35%). In brief, the LVAD outflow cannula location significantly affects the distribution of thrombi in the aorta. Thus, in the clinical practice, the selection of outflow location of LVAD and the risk of thrombi formed in the left ventricle should be paid more attention than before.